Identification of novel bioactive proteins and their produced oligopeptides from Torreya grandis nuts using proteomic based prediction - Durrani Rabia; Meiyun Yang; Yang Baoru; Durand Erwann; Delavault André; Bowen Hou; Weiwei Huan; Yiyang Long; Lili Song; Fei Gao (Elsevier Ltd, 2025)
Torreya grandis nut is a chief functional food in China consumed for centuries. Besides its rich protein composition, increasing studies are now focusing on T. grandis functional proteins that have not yet identified. In this study, liquid chromatography coupled with mass spectrometry detection of smaller and major proteins, revealed that the major peptide was 36935.00 Da. Proteome sequencing annotated 142 proteins in total. Bioactive proteins such as defensin 4 was annotated and its anti-microbial function was verified. Finally, functional oligopeptides were predicted by searching sequences of digested peptides in databases. Ten group of oligopeptides were suggested to exhibit antioxidant, Angiotensin-converting enzyme inhibition, anti-inflammatory. The predicted antioxidant activity was experimentally validated. It is interesting that a peptide GYCVSDNN digested from defensin 4 showed antioxidant activity. This study reports novel functional peptides from T. grandis nuts that have not been isolated and/or included as functional ingredients in nutraceuticals and in food industry.